Narrative Structure in Megg Shaffer’s The Wishing Game : Narrative Structure in Megg Shaffer’s The Wishing Game - Taqwani, Ria; Supsiadji, Mateus Rudi (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
The Wishing Game with a focus on the psychological transformation of the main character, Lucy Hart, in her struggle to become a mother. The problems raised in this study are how the phases of narrative structure according to Tzvetan Todorov’s theory form the tension of the story and character development, as well as how Lucy experiences the transformation of identity as a mother through her narrative experience. The research method used is descriptive qualitative with structuralism and psychological approaches. Data were collected from the text of the novel and analyzed with reference to Todorov’s theory of narrative structure, the theory of matresence by Dr. Aurelie Athan, and the theory of narrative identity by Dan P. McAdams. The analysis shows that Todorov’ five stage narrative structure of equilibrium, disruption, recognition, attempt to repair, and new equilibrium forms the flow of Lucy’s character development gradually. Disruption occurs when Lucy fails to adopt Christopher due to economic conditions, which triggers inner conflict and the urge to change. Her attempt to repair is seen in her participation in a competition that symbolizes her struggle as a mother to be. Matresence theory shows that Lucy experiences an emotional and identity transition towards motherhood, even though it is not yet legal. Meanwhile, through McAdams narrative identity theory, it is revealed that Lucy rewrites her life narrative from a past full of wounds to a story of love, hope and forgiveness. The conclusion of this research is that the narrative structure in The Wishing Game not only functions as a series of events, but also as a place for the emotional development and identity of the main character.